2016
DOI: 10.1097/qad.0000000000000993
|View full text |Cite
|
Sign up to set email alerts
|

Steroids are a risk factor for Kaposi's sarcoma-immune reconstitution inflammatory syndrome and mortality in HIV infection

Abstract: Objectives:To investigate the association between Kaposi's sarcoma-associated immune reconstitution inflammatory syndrome (KS-IRIS) and mortality, with the use of glucocorticoids in HIV-infected individuals.Design:Case–control study.Methods:We reviewed the medical records of 145 individuals with HIV-associated Kaposi's sarcoma receiving antiretroviral therapy. The association of different variables with KS-IRIS and Kaposi's sarcoma-related mortality was explored by univariate and multivariate analyses. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 25 publications
1
25
0
1
Order By: Relevance
“…A number of clinical studies have confirmed that glucocorticoids could increase the incidence, accelerate the progression and increase the mortality of KS in HIV-infected individuals. For these reasons, glucocorticoids are not recommended for AIDS-related KS patients [ 14 , 17 , 18 ]. Liposomal doxorubicin and cART were administrated for this patient of KS complicated with HPS rather than glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical studies have confirmed that glucocorticoids could increase the incidence, accelerate the progression and increase the mortality of KS in HIV-infected individuals. For these reasons, glucocorticoids are not recommended for AIDS-related KS patients [ 14 , 17 , 18 ]. Liposomal doxorubicin and cART were administrated for this patient of KS complicated with HPS rather than glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggest that AIDS-KS cells have high levels of glucocorticoid receptor proteins. Retrospective analysis has confirmed steroid use as a risk factor for KS associated mortality [13,14]. Therefore, physicians should use caution when treating patients for AIH-associated IRIS with prednisone who have a history of HIV-associated Kaposi' sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Initiation of ART may result in immune reconstitution inflammatory syndrome (IRIS) within 3 to 6 months in a reported 6%-39% of patients with AIDS-related Kaposi sarcoma. [79][80][81][82] IRIS is characterized by marked lesional swelling, increased tenderness, and peripheral edema. Individuals with pulmonary involvement, concurrent or recent use of glucocorticoids, and/or advanced immunosuppression may be at increased risk.…”
Section: Antiretroviral Therapymentioning
confidence: 99%
“…Individuals with pulmonary involvement, concurrent or recent use of glucocorticoids, and/or advanced immunosuppression may be at increased risk. 79,80,82 In contrast with management of IRIS for some opportunistic infections, glucocorticoids are generally contraindicated in Kaposi sarcoma, as well as in Kaposi sarcoma-associated IRIS, because of the potential for life-threatening Kaposi sarcoma exacerbation resulting from stimulatory effects of glucocorticoids on Kaposi sarcoma spindle cells. 83,84 Management of Kaposi sarcoma-associated IRIS should involve coordination with an HIV specialist.…”
Section: Antiretroviral Therapymentioning
confidence: 99%